Rate-dependent Ca(2+) signalling underlying the force-frequency response in rat ventricular myocytes: a coupled electromechanical modeling study - Krishna, Abhilash (BioMed Central, 2013)
BACKGROUND: Rate-dependent effects on the Ca(2+) sub-system in a rat ventricular myocyte are investigated. Here, we employ a deterministic mathematical model describing various Ca(2+) signalling pathways under voltage clamp (VC) conditions, to better understand the important role of calmodulin (CaM) in modulating the key control variables Ca(2+)/calmodulin-dependent protein kinase-II (CaMKII), calcineurin (CaN), and cyclic adenosine monophosphate (cAMP) as they affect various intracellular targets. In particular, we study the frequency dependence of the peak force generated by the myofilaments, the force-frequency response (FFR). METHODS: Our cell model incorporates frequency-dependent CaM-mediated spatially heterogenous interaction of CaMKII and CaN with their principal targets (dihydropyridine (DHPR) and ryanodine (RyR) receptors and the SERCA pump). It also accounts for the rate-dependent effects of phospholamban (PLB) on the SERCA pump; the rate-dependent role of cAMP in up-regulation of the L-type Ca(2+) channel (I(Ca,L)); and the enhancement in SERCA pump activity via phosphorylation of PLB. RESULTS: Our model reproduces positive peak FFR observed in rat ventricular myocytes during voltage-clamp studies both in the presence/absence of cAMP mediated β-adrenergic stimulation. This study provides quantitative insight into the rate-dependence of Ca(2+)-induced Ca(2+)-release (CICR) by investigating the frequency-dependence of the trigger current (I(Ca,L)) and RyR-release. It also highlights the relative role of the sodium-calcium exchanger (NCX) and the SERCA pump at higher frequencies, as well as the rate-dependence of sarcoplasmic reticulum (SR) Ca(2+) content. A rigorous Ca(2+) balance imposed on our investigation of these Ca(2+) signalling pathways clarifies their individual roles. Here, we present a coupled electromechanical study emphasizing the rate-dependence of isometric force developed and also investigate the temperature-dependence of FFR. CONCLUSIONS: Our model provides mechanistic biophysically based explanations for the rate-dependence of CICR, generating useful and testable hypotheses. Although rat ventricular myocytes exhibit a positive peak FFR in the presence/absence of beta-adrenergic stimulation, they show a characteristic increase in the positive slope in FFR due to the presence of Norepinephrine or Isoproterenol. Our study identifies cAMP-mediated stimulation, and rate-dependent CaMKII-mediated up-regulation of I(Ca,L) as the key mechanisms underlying the aforementioned positive FFR.